Preliminary results of bivariate analysis in joint Slovenian and Croatian evaluation for milk traits in Holstein breed - Špehar, Marija (Acta agriculturae slovenica. Suplement, 2012)
The objective of this study was to estimate genetic parameters for milk traits (daily milk, fat, and protein yield) for a joint genetic evaluation in Holstein breed in Croatia and Slovenia and to compare results from the joint and national evaluation systems. Test-day records from Croatian (CRO) and Slovenian (SVN) routine genetic evaluation in May 2012 were used. A joint data set included 1,840,816 CRO and 2,680,001 SVN test-day records of 111,218 CRO and 127,774 SVN cows. The total number of animals included in the joint pedigree was 382,991. Genetic parameters for milk traits were estimated using bivariate model. SVN data were evaluated with a model which included fixed effects of calving season and stage of lactation fitted by the Ali-Schaeffer's lactation curve nested within parity. Random part of the model consisted of a common herd environment, direct additive genetic, and permanent environment effect within lactation. In addition to these, fixed class effect of region and covariate age at the first calving were included in the model for CRO data. In the random part, the contemporary group was defined as an interaction between the herd and year of testing for CRO data and as herd effect in SVN data. The estimated heritabilities of daily milk, fat, and protein yield were 0.19, 0.15, and 0.17 for CRO and 0.23, 0.19, and 0.21 for SVN data. Genetic correlation between countries was medium to high (0.78, 0.64, and 0.63) indicating some differences between countries. Correlations between inferred breeding values from the joint and national evaluations were high (0.997 for CRO and 0.999 for SVN evaluation). On SVN scale, genetic trend obtained from the joint evaluation was higher compared to the national evaluation. On CRO scale, the national genetic trend for daily protein yield was similar to the trend from joint model.
Keywords: cattle; correlations; Croatia; genetic trends; genetics; genetika; govedo; heritability; Holstein; lastnosti; milk traits; mleko; Slovenia